The uprooted viewer. Reflections on "Concert for the biocen" by Eugenio Ampudia - Helgueta Manso, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper intends to analyse the work Concert for the biocene (2020) by Eugenio Ampudia. This piece has been not only a musical performance, but also a complex work —concert, performance, installation art, videoart— and a controversial media event. Ampudia has been criticized for his questionable ecological proposal; in addition, some artist accused him of appropriating of the main idea: placing plants on in the proscenium stage. However, the supplanting of the spectator from an aesthetic point of view has not been taken into consideration. In order to achieve this, it is necessary to refer to the postdramatic theory and to think of the pandemic context. This kind of works falls within the category of the postanthropocentric art that anticipates the death of the spectator.
Keywords: Performance; Postdramatic theory; Spectator; Pandemic art; Post-Anthropocentrism